(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Traditional herbal remedy Nyctanthes arbor-tristis offers various therapeutic advantages. It belongs to Oleaceae family and is frequently referred to as “Night Jasmine ". Phytoconstituents were extracted using various solvents, afterwards, they underwent a qualitative analysis. The Agar Plate Diffusion technique was used to investigate the extract’s antibacterial properties. MABA technique of the extract demonstrates sensitivity to the Mycobacterium TB strain (vaccine strain, H37 RV strain). By using GC-MS analysis, ethanolic extract components were identified and characterized. The interpreted compounds were compared to the earlier identified compounds, resulting in the emergence of seven compounds (Calceolarioside A, Betulinic acid,1-(8-Hydroxy-7-((4-nitrophenyl) (phenylamino)methyl) quinoline-3-yl) acetic acid, 1-(8-Hydroxy-7-((4-nitrophenyl) (phenylamino)methyl) quinoline-3-yl) propane-2-one, Lupeol, Arborside B,1-Cyclohexyl-3-(pyridin-3-ylmethyl)urea (cocrystal ligand), C DOCKER software was used to dock those compounds. Among that phytochemicals, the compound Calceolarioside A contained in Nyctanthes arbor-tristis, which exhibits excellent binding energy (-50.9972), C Docker Energy(28.1659), and C Docker Interaction Energy (48.9139).